Teacher’s Role in the Promotion of Two Emotional Intelligence Competencies in Fifth-Grade Children - Villanueva Barbarán, Ruth (2012)
This paper presents the results of a qualitative study aimed at analyzing the teacher’s role in promoting awareness and management of emotions in fifth-graders, as competencies of emotional intelligence. This resulted in a very significant study since, from the psychopedagogic perspective, it aims at breaking with the traditional role of teachers exclusively focused on transmitting knowledge, leaving aside the much-needed emotional support. Children demonstrated a poor vocabulary, as well as difficulty to identify some emotions and differentiate between them. This means a limitation for children to be aware of their own emotions and to control them.  As a conclusion, it is important to maximize the emotional capacities of students; it should be a primary task in the education centers, where teachers play a key role as a model and as a promoter of emotional intelligence.